Encounters with Islam : on religion, politics and modernity - Ruthven, Malise (London : I.B. Tauris, 2012)
For many years Malise Ruthven has been at the forefront of discerning commentary on the Islamic world and its relations with the predominantly secularised and Christian societies of the West. Well known for his bold interventions on such issues as the Rushdie affair and publication of The Satanic Verses; the many unresolved questions relating to the Lockerbie bombing; and the globe-changing terrorist attack of 9/11, Ruthven's perceptive writings, particularly those that have appeared in the "New York Review of Books", reliably re-frame difficult issues and problems so that his readers are prompted to look at the challenges afresh. Ruthven is here at his most compelling: he offers astute and topical insights across the whole spectrum of Middle East and Islamic studies. Whether questioning the involvement of Libyan agents in the downing of Pan Am Flight 103; exploring the contested place of women in Islam; or discussing the disputed term Islamofascism (his own), the author's probing, searchlight intelligence aims always to get at the truth of things, regardless of attendant controversy.--provided by publisher.
A clash of civilisations? -- Faith, power and terror -- Muslim societies -- Iran in focus -- Islam in the West -- Beyond Islam.
Includes bibliographical references and index.
Keywords: Islam; Culture conflict; Islam -- Relations; Islamic fundamentalism; East and West; Islam and state